:: by Czes{\l}aw Byli\'nski and Mariusz \.Zynel

::

:: Received June 22, 1999

:: Copyright (c) 1999-2016 Association of Mizar Users

Lm1: for n being Nat st 1 <= n holds

(n -' 1) + 2 = n + 1

proof end;

theorem Th1: :: JORDAN9:1

for T being non empty TopSpace

for B, C1, C2, D being Subset of T st B is connected & C1 is_a_component_of D & C2 is_a_component_of D & B meets C1 & B meets C2 & B c= D holds

C1 = C2

for B, C1, C2, D being Subset of T st B is connected & C1 is_a_component_of D & C2 is_a_component_of D & B meets C1 & B meets C2 & B c= D holds

C1 = C2

proof end;

theorem Th2: :: JORDAN9:2

for D being non empty set

for f, g being FinSequence of D st ( for n being Nat holds f | n = g | n ) holds

f = g

for f, g being FinSequence of D st ( for n being Nat holds f | n = g | n ) holds

f = g

proof end;

theorem Th3: :: JORDAN9:3

for n being Nat

for D being non empty set

for f being FinSequence of D st n in dom f holds

ex k being Nat st

( k in dom (Rev f) & n + k = (len f) + 1 & f /. n = (Rev f) /. k )

for D being non empty set

for f being FinSequence of D st n in dom f holds

ex k being Nat st

( k in dom (Rev f) & n + k = (len f) + 1 & f /. n = (Rev f) /. k )

proof end;

theorem Th4: :: JORDAN9:4

for n being Nat

for D being non empty set

for f being FinSequence of D st n in dom (Rev f) holds

ex k being Nat st

( k in dom f & n + k = (len f) + 1 & (Rev f) /. n = f /. k )

for D being non empty set

for f being FinSequence of D st n in dom (Rev f) holds

ex k being Nat st

( k in dom f & n + k = (len f) + 1 & (Rev f) /. n = f /. k )

proof end;

theorem Th5: :: JORDAN9:5

for D being non empty set

for G being Matrix of D

for f being FinSequence of D holds

( f is_sequence_on G iff Rev f is_sequence_on G )

for G being Matrix of D

for f being FinSequence of D holds

( f is_sequence_on G iff Rev f is_sequence_on G )

proof end;

theorem Th6: :: JORDAN9:6

for G being Matrix of (TOP-REAL 2)

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G holds

for k being Nat st 1 <= k & k <= len f holds

f /. k in Values G

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G holds

for k being Nat st 1 <= k & k <= len f holds

f /. k in Values G

proof end;

Lm2: for k being Nat

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G & 1 <= k & k <= len f holds

ex i, j being Nat st

( [i,j] in Indices G & f /. k = G * (i,j) )

proof end;

theorem Th7: :: JORDAN9:7

for n being Nat

for f being FinSequence of (TOP-REAL 2)

for x being set st n <= len f & x in L~ (f /^ n) holds

ex i being Nat st

( n + 1 <= i & i + 1 <= len f & x in LSeg (f,i) )

for f being FinSequence of (TOP-REAL 2)

for x being set st n <= len f & x in L~ (f /^ n) holds

ex i being Nat st

( n + 1 <= i & i + 1 <= len f & x in LSeg (f,i) )

proof end;

theorem Th8: :: JORDAN9:8

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G holds

for k being Nat st 1 <= k & k + 1 <= len f holds

( f /. k in left_cell (f,k,G) & f /. k in right_cell (f,k,G) )

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G holds

for k being Nat st 1 <= k & k + 1 <= len f holds

( f /. k in left_cell (f,k,G) & f /. k in right_cell (f,k,G) )

proof end;

theorem Th9: :: JORDAN9:9

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G holds

for k being Nat st 1 <= k & k + 1 <= len f holds

( Int (left_cell (f,k,G)) <> {} & Int (right_cell (f,k,G)) <> {} )

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G holds

for k being Nat st 1 <= k & k + 1 <= len f holds

( Int (left_cell (f,k,G)) <> {} & Int (right_cell (f,k,G)) <> {} )

proof end;

theorem Th10: :: JORDAN9:10

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G holds

for k being Nat st 1 <= k & k + 1 <= len f holds

( Int (left_cell (f,k,G)) is convex & Int (right_cell (f,k,G)) is convex )

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G holds

for k being Nat st 1 <= k & k + 1 <= len f holds

( Int (left_cell (f,k,G)) is convex & Int (right_cell (f,k,G)) is convex )

proof end;

theorem Th11: :: JORDAN9:11

for k being Nat

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G & 1 <= k & k + 1 <= len f holds

( Cl (Int (left_cell (f,k,G))) = left_cell (f,k,G) & Cl (Int (right_cell (f,k,G))) = right_cell (f,k,G) )

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G & 1 <= k & k + 1 <= len f holds

( Cl (Int (left_cell (f,k,G))) = left_cell (f,k,G) & Cl (Int (right_cell (f,k,G))) = right_cell (f,k,G) )

proof end;

theorem Th12: :: JORDAN9:12

for k being Nat

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G & LSeg (f,k) is horizontal holds

ex j being Nat st

( 1 <= j & j <= width G & ( for p being Point of (TOP-REAL 2) st p in LSeg (f,k) holds

p `2 = (G * (1,j)) `2 ) )

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G & LSeg (f,k) is horizontal holds

ex j being Nat st

( 1 <= j & j <= width G & ( for p being Point of (TOP-REAL 2) st p in LSeg (f,k) holds

p `2 = (G * (1,j)) `2 ) )

proof end;

theorem Th13: :: JORDAN9:13

for k being Nat

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G & LSeg (f,k) is vertical holds

ex i being Nat st

( 1 <= i & i <= len G & ( for p being Point of (TOP-REAL 2) st p in LSeg (f,k) holds

p `1 = (G * (i,1)) `1 ) )

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G & LSeg (f,k) is vertical holds

ex i being Nat st

( 1 <= i & i <= len G & ( for p being Point of (TOP-REAL 2) st p in LSeg (f,k) holds

p `1 = (G * (i,1)) `1 ) )

proof end;

theorem Th14: :: JORDAN9:14

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G & f is special holds

for i, j being Nat st i <= len G & j <= width G holds

Int (cell (G,i,j)) misses L~ f

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G & f is special holds

for i, j being Nat st i <= len G & j <= width G holds

Int (cell (G,i,j)) misses L~ f

proof end;

theorem Th15: :: JORDAN9:15

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G & f is special holds

for k being Nat st 1 <= k & k + 1 <= len f holds

( Int (left_cell (f,k,G)) misses L~ f & Int (right_cell (f,k,G)) misses L~ f )

for f being FinSequence of (TOP-REAL 2) st f is_sequence_on G & f is special holds

for k being Nat st 1 <= k & k + 1 <= len f holds

( Int (left_cell (f,k,G)) misses L~ f & Int (right_cell (f,k,G)) misses L~ f )

proof end;

theorem Th16: :: JORDAN9:16

for i, j being Nat

for G being Go-board st 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G holds

( (G * (i,j)) `1 = (G * (i,(j + 1))) `1 & (G * (i,j)) `2 = (G * ((i + 1),j)) `2 & (G * ((i + 1),(j + 1))) `1 = (G * ((i + 1),j)) `1 & (G * ((i + 1),(j + 1))) `2 = (G * (i,(j + 1))) `2 )

for G being Go-board st 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G holds

( (G * (i,j)) `1 = (G * (i,(j + 1))) `1 & (G * (i,j)) `2 = (G * ((i + 1),j)) `2 & (G * ((i + 1),(j + 1))) `1 = (G * ((i + 1),j)) `1 & (G * ((i + 1),(j + 1))) `2 = (G * (i,(j + 1))) `2 )

proof end;

theorem Th17: :: JORDAN9:17

for G being Go-board

for p being Point of (TOP-REAL 2)

for i, j being Nat st 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G holds

( p in cell (G,i,j) iff ( (G * (i,j)) `1 <= p `1 & p `1 <= (G * ((i + 1),j)) `1 & (G * (i,j)) `2 <= p `2 & p `2 <= (G * (i,(j + 1))) `2 ) )

for p being Point of (TOP-REAL 2)

for i, j being Nat st 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G holds

( p in cell (G,i,j) iff ( (G * (i,j)) `1 <= p `1 & p `1 <= (G * ((i + 1),j)) `1 & (G * (i,j)) `2 <= p `2 & p `2 <= (G * (i,(j + 1))) `2 ) )

proof end;

theorem :: JORDAN9:18

for i, j being Nat

for G being Go-board st 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G holds

cell (G,i,j) = { |[r,s]| where r, s is Real : ( (G * (i,j)) `1 <= r & r <= (G * ((i + 1),j)) `1 & (G * (i,j)) `2 <= s & s <= (G * (i,(j + 1))) `2 ) }

for G being Go-board st 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G holds

cell (G,i,j) = { |[r,s]| where r, s is Real : ( (G * (i,j)) `1 <= r & r <= (G * ((i + 1),j)) `1 & (G * (i,j)) `2 <= s & s <= (G * (i,(j + 1))) `2 ) }

proof end;

theorem Th19: :: JORDAN9:19

for i, j being Nat

for G being Go-board

for p being Point of (TOP-REAL 2) st 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G & p in Values G & p in cell (G,i,j) & not p = G * (i,j) & not p = G * (i,(j + 1)) & not p = G * ((i + 1),(j + 1)) holds

p = G * ((i + 1),j)

for G being Go-board

for p being Point of (TOP-REAL 2) st 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G & p in Values G & p in cell (G,i,j) & not p = G * (i,j) & not p = G * (i,(j + 1)) & not p = G * ((i + 1),(j + 1)) holds

p = G * ((i + 1),j)

proof end;

theorem Th20: :: JORDAN9:20

for i, j being Nat

for G being Go-board st 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G holds

( G * (i,j) in cell (G,i,j) & G * (i,(j + 1)) in cell (G,i,j) & G * ((i + 1),(j + 1)) in cell (G,i,j) & G * ((i + 1),j) in cell (G,i,j) )

for G being Go-board st 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G holds

( G * (i,j) in cell (G,i,j) & G * (i,(j + 1)) in cell (G,i,j) & G * ((i + 1),(j + 1)) in cell (G,i,j) & G * ((i + 1),j) in cell (G,i,j) )

proof end;

theorem Th21: :: JORDAN9:21

for i, j being Nat

for G being Go-board

for p being Point of (TOP-REAL 2) st 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G & p in Values G & p in cell (G,i,j) holds

p is_extremal_in cell (G,i,j)

for G being Go-board

for p being Point of (TOP-REAL 2) st 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G & p in Values G & p in cell (G,i,j) holds

p is_extremal_in cell (G,i,j)

proof end;

theorem Th22: :: JORDAN9:22

for k being Nat

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st 2 <= len G & 2 <= width G & f is_sequence_on G & 1 <= k & k + 1 <= len f holds

ex i, j being Nat st

( 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G & LSeg (f,k) c= cell (G,i,j) )

for G being Go-board

for f being FinSequence of (TOP-REAL 2) st 2 <= len G & 2 <= width G & f is_sequence_on G & 1 <= k & k + 1 <= len f holds

ex i, j being Nat st

( 1 <= i & i + 1 <= len G & 1 <= j & j + 1 <= width G & LSeg (f,k) c= cell (G,i,j) )

proof end;

theorem Th23: :: JORDAN9:23

for k being Nat

for G being Go-board

for f being FinSequence of (TOP-REAL 2)

for p being Point of (TOP-REAL 2) st 2 <= len G & 2 <= width G & f is_sequence_on G & 1 <= k & k + 1 <= len f & p in Values G & p in LSeg (f,k) & not p = f /. k holds

p = f /. (k + 1)

for G being Go-board

for f being FinSequence of (TOP-REAL 2)

for p being Point of (TOP-REAL 2) st 2 <= len G & 2 <= width G & f is_sequence_on G & 1 <= k & k + 1 <= len f & p in Values G & p in LSeg (f,k) & not p = f /. k holds

p = f /. (k + 1)

proof end;

theorem :: JORDAN9:24

for i, j, k being Nat

for G being Go-board st [i,j] in Indices G & 1 <= k & k <= width G holds

(G * (i,j)) `1 <= (G * ((len G),k)) `1

for G being Go-board st [i,j] in Indices G & 1 <= k & k <= width G holds

(G * (i,j)) `1 <= (G * ((len G),k)) `1

proof end;

theorem :: JORDAN9:25

for i, j, k being Nat

for G being Go-board st [i,j] in Indices G & 1 <= k & k <= len G holds

(G * (i,j)) `2 <= (G * (k,(width G))) `2

for G being Go-board st [i,j] in Indices G & 1 <= k & k <= len G holds

(G * (i,j)) `2 <= (G * (k,(width G))) `2

proof end;

theorem Th26: :: JORDAN9:26

for k being Nat

for G being Go-board

for f, g being FinSequence of (TOP-REAL 2) st f is_sequence_on G & f is special & L~ g c= L~ f & 1 <= k & k + 1 <= len f holds

for A being Subset of (TOP-REAL 2) st ( A = (right_cell (f,k,G)) \ (L~ g) or A = (left_cell (f,k,G)) \ (L~ g) ) holds

A is connected

for G being Go-board

for f, g being FinSequence of (TOP-REAL 2) st f is_sequence_on G & f is special & L~ g c= L~ f & 1 <= k & k + 1 <= len f holds

for A being Subset of (TOP-REAL 2) st ( A = (right_cell (f,k,G)) \ (L~ g) or A = (left_cell (f,k,G)) \ (L~ g) ) holds

A is connected

proof end;

theorem Th27: :: JORDAN9:27

for G being Go-board

for f being non constant standard special_circular_sequence st f is_sequence_on G holds

for k being Nat st 1 <= k & k + 1 <= len f holds

( (right_cell (f,k,G)) \ (L~ f) c= RightComp f & (left_cell (f,k,G)) \ (L~ f) c= LeftComp f )

for f being non constant standard special_circular_sequence st f is_sequence_on G holds

for k being Nat st 1 <= k & k + 1 <= len f holds

( (right_cell (f,k,G)) \ (L~ f) c= RightComp f & (left_cell (f,k,G)) \ (L~ f) c= LeftComp f )

proof end;

theorem Th28: :: JORDAN9:28

for C being non empty compact non horizontal non vertical Subset of (TOP-REAL 2)

for n being Nat ex i being Nat st

( 1 <= i & i + 1 <= len (Gauge (C,n)) & N-min C in cell ((Gauge (C,n)),i,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i,((width (Gauge (C,n))) -' 1)) )

for n being Nat ex i being Nat st

( 1 <= i & i + 1 <= len (Gauge (C,n)) & N-min C in cell ((Gauge (C,n)),i,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i,((width (Gauge (C,n))) -' 1)) )

proof end;

theorem Th29: :: JORDAN9:29

for C being non empty compact non horizontal non vertical Subset of (TOP-REAL 2)

for n, i1, i2 being Nat st 1 <= i1 & i1 + 1 <= len (Gauge (C,n)) & N-min C in cell ((Gauge (C,n)),i1,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i1,((width (Gauge (C,n))) -' 1)) & 1 <= i2 & i2 + 1 <= len (Gauge (C,n)) & N-min C in cell ((Gauge (C,n)),i2,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i2,((width (Gauge (C,n))) -' 1)) holds

i1 = i2

for n, i1, i2 being Nat st 1 <= i1 & i1 + 1 <= len (Gauge (C,n)) & N-min C in cell ((Gauge (C,n)),i1,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i1,((width (Gauge (C,n))) -' 1)) & 1 <= i2 & i2 + 1 <= len (Gauge (C,n)) & N-min C in cell ((Gauge (C,n)),i2,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i2,((width (Gauge (C,n))) -' 1)) holds

i1 = i2

proof end;

theorem Th30: :: JORDAN9:30

for C being non empty compact non horizontal non vertical Subset of (TOP-REAL 2)

for n being Nat

for f being non constant standard special_circular_sequence st f is_sequence_on Gauge (C,n) & ( for k being Nat st 1 <= k & k + 1 <= len f holds

( left_cell (f,k,(Gauge (C,n))) misses C & right_cell (f,k,(Gauge (C,n))) meets C ) ) & ex i being Nat st

( 1 <= i & i + 1 <= len (Gauge (C,n)) & f /. 1 = (Gauge (C,n)) * (i,(width (Gauge (C,n)))) & f /. 2 = (Gauge (C,n)) * ((i + 1),(width (Gauge (C,n)))) & N-min C in cell ((Gauge (C,n)),i,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i,((width (Gauge (C,n))) -' 1)) ) holds

N-min (L~ f) = f /. 1

for n being Nat

for f being non constant standard special_circular_sequence st f is_sequence_on Gauge (C,n) & ( for k being Nat st 1 <= k & k + 1 <= len f holds

( left_cell (f,k,(Gauge (C,n))) misses C & right_cell (f,k,(Gauge (C,n))) meets C ) ) & ex i being Nat st

( 1 <= i & i + 1 <= len (Gauge (C,n)) & f /. 1 = (Gauge (C,n)) * (i,(width (Gauge (C,n)))) & f /. 2 = (Gauge (C,n)) * ((i + 1),(width (Gauge (C,n)))) & N-min C in cell ((Gauge (C,n)),i,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i,((width (Gauge (C,n))) -' 1)) ) holds

N-min (L~ f) = f /. 1

proof end;

definition

let C be non empty compact non horizontal non vertical Subset of (TOP-REAL 2);

let n be Nat;

assume A1: C is connected ;

ex b_{1} being non constant standard clockwise_oriented special_circular_sequence st

( b_{1} is_sequence_on Gauge (C,n) & ex i being Nat st

( 1 <= i & i + 1 <= len (Gauge (C,n)) & b_{1} /. 1 = (Gauge (C,n)) * (i,(width (Gauge (C,n)))) & b_{1} /. 2 = (Gauge (C,n)) * ((i + 1),(width (Gauge (C,n)))) & N-min C in cell ((Gauge (C,n)),i,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i,((width (Gauge (C,n))) -' 1)) ) & ( for k being Nat st 1 <= k & k + 2 <= len b_{1} holds

( ( front_left_cell (b_{1},k,(Gauge (C,n))) misses C & front_right_cell (b_{1},k,(Gauge (C,n))) misses C implies b_{1} turns_right k, Gauge (C,n) ) & ( front_left_cell (b_{1},k,(Gauge (C,n))) misses C & front_right_cell (b_{1},k,(Gauge (C,n))) meets C implies b_{1} goes_straight k, Gauge (C,n) ) & ( front_left_cell (b_{1},k,(Gauge (C,n))) meets C implies b_{1} turns_left k, Gauge (C,n) ) ) ) )

for b_{1}, b_{2} being non constant standard clockwise_oriented special_circular_sequence st b_{1} is_sequence_on Gauge (C,n) & ex i being Nat st

( 1 <= i & i + 1 <= len (Gauge (C,n)) & b_{1} /. 1 = (Gauge (C,n)) * (i,(width (Gauge (C,n)))) & b_{1} /. 2 = (Gauge (C,n)) * ((i + 1),(width (Gauge (C,n)))) & N-min C in cell ((Gauge (C,n)),i,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i,((width (Gauge (C,n))) -' 1)) ) & ( for k being Nat st 1 <= k & k + 2 <= len b_{1} holds

( ( front_left_cell (b_{1},k,(Gauge (C,n))) misses C & front_right_cell (b_{1},k,(Gauge (C,n))) misses C implies b_{1} turns_right k, Gauge (C,n) ) & ( front_left_cell (b_{1},k,(Gauge (C,n))) misses C & front_right_cell (b_{1},k,(Gauge (C,n))) meets C implies b_{1} goes_straight k, Gauge (C,n) ) & ( front_left_cell (b_{1},k,(Gauge (C,n))) meets C implies b_{1} turns_left k, Gauge (C,n) ) ) ) & b_{2} is_sequence_on Gauge (C,n) & ex i being Nat st

( 1 <= i & i + 1 <= len (Gauge (C,n)) & b_{2} /. 1 = (Gauge (C,n)) * (i,(width (Gauge (C,n)))) & b_{2} /. 2 = (Gauge (C,n)) * ((i + 1),(width (Gauge (C,n)))) & N-min C in cell ((Gauge (C,n)),i,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i,((width (Gauge (C,n))) -' 1)) ) & ( for k being Nat st 1 <= k & k + 2 <= len b_{2} holds

( ( front_left_cell (b_{2},k,(Gauge (C,n))) misses C & front_right_cell (b_{2},k,(Gauge (C,n))) misses C implies b_{2} turns_right k, Gauge (C,n) ) & ( front_left_cell (b_{2},k,(Gauge (C,n))) misses C & front_right_cell (b_{2},k,(Gauge (C,n))) meets C implies b_{2} goes_straight k, Gauge (C,n) ) & ( front_left_cell (b_{2},k,(Gauge (C,n))) meets C implies b_{2} turns_left k, Gauge (C,n) ) ) ) holds

b_{1} = b_{2}

end;
let n be Nat;

assume A1: C is connected ;

func Cage (C,n) -> non constant standard clockwise_oriented special_circular_sequence means :Def1: :: JORDAN9:def 1

( it is_sequence_on Gauge (C,n) & ex i being Nat st

( 1 <= i & i + 1 <= len (Gauge (C,n)) & it /. 1 = (Gauge (C,n)) * (i,(width (Gauge (C,n)))) & it /. 2 = (Gauge (C,n)) * ((i + 1),(width (Gauge (C,n)))) & N-min C in cell ((Gauge (C,n)),i,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i,((width (Gauge (C,n))) -' 1)) ) & ( for k being Nat st 1 <= k & k + 2 <= len it holds

( ( front_left_cell (it,k,(Gauge (C,n))) misses C & front_right_cell (it,k,(Gauge (C,n))) misses C implies it turns_right k, Gauge (C,n) ) & ( front_left_cell (it,k,(Gauge (C,n))) misses C & front_right_cell (it,k,(Gauge (C,n))) meets C implies it goes_straight k, Gauge (C,n) ) & ( front_left_cell (it,k,(Gauge (C,n))) meets C implies it turns_left k, Gauge (C,n) ) ) ) );

existence ( it is_sequence_on Gauge (C,n) & ex i being Nat st

( 1 <= i & i + 1 <= len (Gauge (C,n)) & it /. 1 = (Gauge (C,n)) * (i,(width (Gauge (C,n)))) & it /. 2 = (Gauge (C,n)) * ((i + 1),(width (Gauge (C,n)))) & N-min C in cell ((Gauge (C,n)),i,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i,((width (Gauge (C,n))) -' 1)) ) & ( for k being Nat st 1 <= k & k + 2 <= len it holds

( ( front_left_cell (it,k,(Gauge (C,n))) misses C & front_right_cell (it,k,(Gauge (C,n))) misses C implies it turns_right k, Gauge (C,n) ) & ( front_left_cell (it,k,(Gauge (C,n))) misses C & front_right_cell (it,k,(Gauge (C,n))) meets C implies it goes_straight k, Gauge (C,n) ) & ( front_left_cell (it,k,(Gauge (C,n))) meets C implies it turns_left k, Gauge (C,n) ) ) ) );

ex b

( b

( 1 <= i & i + 1 <= len (Gauge (C,n)) & b

( ( front_left_cell (b

proof end;

uniqueness for b

( 1 <= i & i + 1 <= len (Gauge (C,n)) & b

( ( front_left_cell (b

( 1 <= i & i + 1 <= len (Gauge (C,n)) & b

( ( front_left_cell (b

b

proof end;

:: deftheorem Def1 defines Cage JORDAN9:def 1 :

for C being non empty compact non horizontal non vertical Subset of (TOP-REAL 2)

for n being Nat st C is connected holds

for b_{3} being non constant standard clockwise_oriented special_circular_sequence holds

( b_{3} = Cage (C,n) iff ( b_{3} is_sequence_on Gauge (C,n) & ex i being Nat st

( 1 <= i & i + 1 <= len (Gauge (C,n)) & b_{3} /. 1 = (Gauge (C,n)) * (i,(width (Gauge (C,n)))) & b_{3} /. 2 = (Gauge (C,n)) * ((i + 1),(width (Gauge (C,n)))) & N-min C in cell ((Gauge (C,n)),i,((width (Gauge (C,n))) -' 1)) & N-min C <> (Gauge (C,n)) * (i,((width (Gauge (C,n))) -' 1)) ) & ( for k being Nat st 1 <= k & k + 2 <= len b_{3} holds

( ( front_left_cell (b_{3},k,(Gauge (C,n))) misses C & front_right_cell (b_{3},k,(Gauge (C,n))) misses C implies b_{3} turns_right k, Gauge (C,n) ) & ( front_left_cell (b_{3},k,(Gauge (C,n))) misses C & front_right_cell (b_{3},k,(Gauge (C,n))) meets C implies b_{3} goes_straight k, Gauge (C,n) ) & ( front_left_cell (b_{3},k,(Gauge (C,n))) meets C implies b_{3} turns_left k, Gauge (C,n) ) ) ) ) );

for C being non empty compact non horizontal non vertical Subset of (TOP-REAL 2)

for n being Nat st C is connected holds

for b

( b

( 1 <= i & i + 1 <= len (Gauge (C,n)) & b

( ( front_left_cell (b

theorem Th31: :: JORDAN9:31

for C being non empty compact non horizontal non vertical Subset of (TOP-REAL 2) st C is connected holds

for n, k being Nat st 1 <= k & k + 1 <= len (Cage (C,n)) holds

( left_cell ((Cage (C,n)),k,(Gauge (C,n))) misses C & right_cell ((Cage (C,n)),k,(Gauge (C,n))) meets C )

for n, k being Nat st 1 <= k & k + 1 <= len (Cage (C,n)) holds

( left_cell ((Cage (C,n)),k,(Gauge (C,n))) misses C & right_cell ((Cage (C,n)),k,(Gauge (C,n))) meets C )

proof end;

theorem :: JORDAN9:32

for C being non empty compact non horizontal non vertical Subset of (TOP-REAL 2) st C is connected holds

for n being Nat holds N-min (L~ (Cage (C,n))) = (Cage (C,n)) /. 1

for n being Nat holds N-min (L~ (Cage (C,n))) = (Cage (C,n)) /. 1

proof end;